Debate Methods and Students' Self-Confidence: Correlational Study at PPM Al-Istiqamah Ngatabaru - Nurul Fikra; Nur Asmawati; Zul Aini Rengur (CV. Global Cendekia Inti, 2026)
This research aims to find out how debating affects the level of self-confidence of grade IX students at PPM Al-Istiqomah Ngatabaru school. Debate is an active learning method that encourages students to think critically, express opinions, and interact actively. Deep process Study. StudyThis uses a quantitative, correlational design. The population study consists of 36 students in class IX, which was also used as a sample using the total sampling technique. Data collection was conducted using two questionnaires: the debate method questionnaire and the self-confidence questionnaire, each arranged on a Likert scale. Data were analyzed using descriptive statistical methods, hand Shapiro–Wilk normality tests, and hand Pearson correlation.Studies show that both variables have a normal distribution. Mark significance from the method debate is 0.127, and the confidence level itself is 0.833. The descriptive shows that the score flat-flat for the method debate is 66.69, and the score flat-flat for trust self is 60.56. The results of the Pearson correlation test show a positive, real relationship between the debate method and self-confidence, with a correlation coefficient of r = 0.663 and a significance value of p = 0.001. Findings show that the more the Good method debate is incorporated into a deep-process study, the higher students' self-confidence levels.Studyit offers new discoveries through an analysis of the relationship between debate methods and levels of trust, and of self-deep context education in Islamic boarding schools, which has not been much studied. Results of the study. This can be used by teachers as a reference, deepening the debate over the method as a way of learning that not only helps improve students' academic abilities but also forms character and builds their confidence.